"Are all beliefs equal?" investigating the nature and determinants of parental attitudinal beliefs towards educational inclusion. Issue 5 (20th October 2017) - Sosu, Edward M.; Rydzewska, Ewelina
Abstract: This study explores the nature of parental attitudinal beliefs towards educational inclusion and the factors that determine these beliefs. Participants were drawn from the Growing Up in Scotland Survey ( N = 2200). Results indicate that majority of parents held positive generalised belief towards including children with additional support needs (ASN) in mainstream classrooms (90%), compared with belief about the benefits of inclusion for children with ASN (72%), or benefits for typically developing children (70%). Lower parental income and higher levels of satisfaction with child's current school were associated with positive generalised beliefs. Belief about the benefits of inclusion for children with ASN was also positively associated with lower parental income, while belief about benefits for typically developing children was determined by higher parental education and age. Our findings suggest that efforts to increase parental attitudes should target salient beliefs and take into account the determinants of each of these beliefs.